The aging behavior, microstructure and mechanical properties of AlN/AZ91 composite - Yunxia Sun; Changlin Yang; Bin Zhang; Jianfeng Fan; Hongxiang Li; Tianhao Zhao; Jing Li (Journal of Magnesium and Alloys, 2023)
Microstructure evolution and mechanical properties of the aging treated AlN/AZ91 composites were systematically investigated by optical microscopy (OM), high resolution scanning electron microscopy (HRSEM) with an energy dispersive spectrum (EDS), and high-angle annular dark field scanning transmission electron microscopy (HAADF-STEM). The results show that the higher fracture elongation (14 ± 1%) and ultimate tensile strength (275 ± 6 MPa) were simultaneously obtained in the peak-aged AlN/AZ91 composites. Comparied with AZ91 matrix alloy, the strength was increased by about 44% and the elongation was approximately five times higher, which mainly attributed to the precipitation of nano-sized γ-Mg17Al12 phase and the activation of non-basal slip systems induced by in-situ AlN particles at room temperature. However, the in-situ formation of AlN reinforcements consumed part of Al element in the matrix alloy, which resulted into the volume fraction decreasing of γ-Mg17Al12 precipitates, and then the age hardening and strengthening efficiency were reduced in the AlN/AZ91 composites. On the other hand, the mismatch of thermal expansion coefficient between AlN particles and AZ91 matrix generated high density dislocations around AlN particles, which promoted the precipitation of γ-Mg17Al12 phase, and then the peak aging time and temperature were decreased.